Learning as knowledge networking: conceptual foundations for revised uses of the Internet in higher education - Allen, Matthew; Long, J. (Newswood Limited (for International Association of Engineers, IAENG), 2009)
This paper argues that the inherent characteristics of knowledge work, when combined with the operation of the Internet in contemporary society, produce a change in the dominant paradigm of what constitutes knowledge work. Since learning is a form of knowledge work, therefore this change will affect university education. The paper further argues that, because of the way in which online learning initially developed in universities, in most cases, the current approach to the Internet and higher education does not account for the changed conditions of knowledge in a network society. It concludes that new directions are needed which will allow us to make technology and pedagogy choices for future education better suited to a network society.